Contexto histórico do processo de institucionalização das telecomunicações no Brasil - Kestelman, Hélio Nahmen (2002)
Telecommunications represents one ofthe most relevant sectors ofthe Brazilian social system. It arose, developed and reached highly significant leveIs in Brazil, as well as in the world, always marked by the challenge and the men's need to communicate and to heard at greater and greater distances. In the present days, as a result of the recent brake in the state monopoly, Brazilian telecommunications has been consolidating one more phase of its evolution and, for that, it is necessary to research and try to comprehend the process and the different changes of tendencies that occurred during this trajectory. The Historical Context of the Telecommunications Sector Institutionalization Process is the theme of this document, which, in contrast with studies of institutionalization related to the development of single organizations, treats the sector as a whole, taking into consideration the dynamics of its internaI variables and its relationship with the society. In this context, hypotheses related to a systematic view are applied. In this view, the sector positions itself as a processor, receiving inputs from the externaI environment and returning results in form of services or products. Among many classifications that have been used to define the concept of system, this work will concentrate in the characterization of the Brazilian telecommunications sector as a complex, open and social system. To this end, different stages of the process of institutional development were studied identifying moments of its evolution in the context of its political, economical, social and technological interaction with the Nation. The objeetive ofthis researeh is to deseribe the proeess ofthe seetor evolution through the use of theoretieal subsides and through a eomparative analysis, subjeetive (empirieal), with the eountry development. The ehoiee of this theme eame from the realization of the neeessity to develop from existent studies, merely direeted to historieal faets, to a wider and more integrated approaeh, with the teleeommunieation's responsibilities with the environrnent where it is inserted.